Efficacy of Ultrasonography in Detecting Intestinal and Biliary Ascariasis - Sharma, UK (Health Renaissance, 2011)
Introduction: Ascariasis is a common helminthic infection particularly in the tropics and subtropics. Ultrasound can be a useful tool in the detection of adult intestinal and biliary ascariasis. Objective: To evaluate the efficacy of ultrasonography in intestinal and biliary ascariasis. Methods: A prospective study was designed to evaluate the prevalence incidence, clinical features, and ultrasound findings of intestinal and biliary ascariasis from August 2005 to July 2006. Results: A total of 3000 patients underwent abdominal ultrasonography. In 60 (2%) patients, worm infestation was detected. Intestinal ascariasis was detected in 54 patients and biliary ascariasis in six. Four patients had Common bile duct (CBD) ascariasis, one gall bladder (GB) ascariasis with acute cholecystitis and one had ascaris induced liver abscess. Complications like intussusception and subacute intestinal obstruction were found in one each. Intestinal ascariasis was detected with the use of only high frequency linear transducer. Fifty three patients were treated conservatively, three patients underwent surgery. Endoscopic removal of CBD ascaris was done in four patients, where as in one patient there was spontaneous exit of the worm. Conclusions: Ultrasonography is a very useful method for detection of intestinal and biliary ascariasis. The use of high frequency linear transducer can be used for the detection of intestinal ascariasis. Keywords: ascariasis; ultrasound; common bile duct DOI: 10.3126/hren.v9i1.4353 Health Renaissance, 2011: Vol.9 No.1:3-6